PELAKSANAAN PROGRAM TAHFIDZ ALQURAN - Wasil, Mohammad; Putri, Titalia Diana (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
Baban village has a tahfidz program educational institution that has the magnetic power to attract interest as well as the development of human resources of the local community, especially in terms of religious education such as memorizing the Qur'an. The history of the establishment of the tahfidz program with the Ilan method begins with the anxiety of a hafidzoh named Ahdil Ummamiyah when he saw the children in Baban village playing more than learning, this was what later made him feel called to establish the tahfidz program in the Baban hamlet. The tahfidz program is held 3 times a day, at the dawn, the Asr, and the evening. The method used in this program is the Ilan method and rewards for those who have progressed in memorizing and giving punishment when not adding to the memorization of the Koran. The Baban Hamlet community is very enthusiastic about supporting this program by participating in the implementation of the Ilan method. This research shows that the holding of the Tahfidz program in the Baban hamlet can build citizens' concern for children who memorize the Qur'an. Al-Qur'an is a source of Islamic law that can bring calm to those who read and practice it especially for those who can memorize it. This study discusses the implementation of the Tahfidz program in the village of Baban. This study uses a qualitative-descriptive approach with the method of extracting observational data, interviews, and documentation. With a focus of research: First, the history of the establishment of the Tahfidz program in the village of Baban. Second, the implementation of the tahfidz program with the Ilan method. Third, the community response to the Tahfidz program in the Baban village. Fourth, the impact on children who take part in the Tahfidz program in Baban sub-village. This research is important because the researcher tries to describe how the implementation of the Tahfidz program in the hamlet of Baban. This research is also interesting because the researchers also tried to describe how the response of the Baban hamlet community to the Tahfidz program.